Analysis and Control of Modular Multi-terminal DC Power Flow Controller with Fault Current Limiting Function - Qianming Xu (IEEE, 2021)
In order to overcome the problems of power flow control and fault current limiting in multi-terminal high voltage direct current (MTDC) grids, this paper proposes a modular multi-terminal DC power flow controller (MM-DCPFC) with fault current limiting function. The topology structure, operation principle, and equivalent circuit of MM-DCPFC are introduced, and such a structure has the advantages of modularity and scalability. The power balance mechanism is studied and a hierarchical power balance control strategy is proposed. The results show that MM-DCPFC can achieve internal power exchange, which avoids the use of external power supply. The fault characteristics of MM-DCPFC are analyzed, fault current limiting and self-protection methods are proposed, and the factors affecting the current limiting capability are studied. The simulation models are established in PLECS, and the simulation results verify the effectiveness of MM-DCPFC in power flow control, fault current limiting, and scalability. In addition, a prototype is developed to validate the function and control method of MM-DCPFC.